P27 Evaluation and baseline characteristics of patients with chronic thromboembolic disease in a single referral centre. (15th November 2016) - Swietlik, EM; Taboada, D; Ruggiero, A; Bales, E; Harlow, L; Fletcher, A; Cannon, JE; Sheares, K; Jenkins, DP; Pepke-Zaba, J; Toshner, M
Abstract : Introduction: Chronic thromboembolic disease (CTED) is a consequence of failure of thrombus resolution following pulmonary embolism. Thrombotic material becomes fibrosed, resulting in chronic vascular occlusion without pulmonary hypertension. The prevalence and incidence of the condition is unknown and the mechanisms behind exercise intolerance are poorly understood. Surgical management in selected cases may significantly improve symptoms and patient functioning. 1 Methods: We prospectively evaluated baseline characteristics of patients with CTED in a single referral centre between January 2015 and June 2016. Newly referred patients with suspected CTED underwent a standard assessment as delineated in international guidelines with a minimum of 2 imaging modalities, resting and exercise right heart catheterisation and additionally incremental cardiopulmonary exercise testing (CPET). All patients were assessed in a pulmonary endarterectomy (PEA) MDT. Results: 128 patients were diagnosed with CTEPH or CTED from our referral centre. 28 patients were referred with suspected CTED due to ECHO findings. Of these 21 patients were confirmed to have CTED at right heart catheterization and 16 underwent full investigation protocol and were analysed. Patients with CTED were younger than contemporary cohorts of CTEPH 2 and were more likely to have a past medical history of VTE (94%). Patients with CTED had normal resting haemodynamics, preserved RV function at rest and normal NT-proBNP (Table1). After careful review of each patient's investigations only 5 of the 21 patients with CTED were offered PEA. Conclusions: Patients with CTED represent a significant proportion of the new referrals to our specialist centre. Surgery is deemed an appropriate therapeutic approach in a small subset of patients with significant functional and symptomatic impairment. The natural history of CTED is unclear so any discussion of surgery needs to carefully consider surgical risk of death and morbidity against the potential for symptomatic improvement. References: Taboada D, et al . Outcome of pulmonary endarterctomy in symptomatic chronic thromboembolic disease. ERJ 2014;44 (6):1635–45. Pepke-Zaba J, et al . Chronic Thromboembolic Pulmonary Hypertension (CTEPH): Results from and international prospective registry. Circulation 2011;124 (18):1973–81.